TINJAUAN YURIDIS UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA TERHADAP KARYA CIPTA LAGU YANG DIARANSEMEN ULANG TANPA IZIN PENCIPTA - I.B Nym Adhyka Crismantara; Ni Komang Ratih Kumala Dewi (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2021)
A phenomenon that is rife in the community lately, namely the arrangement of a work of songwriting. Implementation of Law No. 28 of 2014 until now there are still many violations, especially in the form of acts of rearranging songs without the author's permission. This copyright infringement has reached a dangerous level and can damage the fabric of people's lives in general and the interest to create in particular. The formulation of the problem in this study is how to regulate the work of songwriting that is rearranged without the author's permission according to Law no. 28 of 2014 concerning copyright and how is the legal protection of song copyrighted works that are rearranged without the author's permission according to Law no. 28 of 2014 concerning copyright. The conclusion of this research is that the regulation of copyright for songwriting works in Indonesia is regulated in Law No. 28 of 2014 concerning copyright and forms of legal protection for song-writing works in Law no. 28 of 2014 concerning Copyright, namely preventive legal protection and repressive legal protection.